Graphene composite perovskite manganite polycrystalline ceramic, preparation method and application thereof

CN119569453BActive Publication Date: 2026-10-30KUNMING UNIV OF SCI & TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411769440.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-04
Publication Date
2026-10-30
Estimated Expiration
2044-12-04

AI Technical Summary

Technical Problem

[0003]目前,钙钛矿锰氧化物主要分为ABO3型和A2BO4型两种类型,两种类型的钙钛矿锰氧化物在结构上存在显著区别,本发明的钙钛矿锰氧化物属于ABO3型,而由于ABO3型钙钛矿锰氧化物的晶界处存在缺陷和杂质,会影响其电输运性能,导致其晶界处的电阻率较高,载流子在通过这些区域时,会受到散射效应干扰,使巡游电子迁移率降低,导致ABO3型钙钛矿锰氧化物对TCR和Tk的调控效果受到限制,无法有效发挥多晶陶瓷在室温条件下对温度变化的高敏感性,影响非制冷红外探测器探测的精准度

Benefits of technology

[0023]1.本发明石墨烯以第二相复合进入La0.81(Ca0.03Sr0.16)MnO3陶瓷,并且在陶瓷中的存在形式以晶界富集为主,石墨烯可以在晶粒边界形成导电通道,有利于电子传导,改善晶界处的电荷传输行为,改善多晶陶瓷的晶界效应,钝化晶界处缺陷态,诱导改善多晶陶瓷结晶质量,增强晶粒间载流子迁移效率,显著提升多晶陶瓷导电性能,从而使多晶陶瓷TCR值得到提高。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119569453B_ABST
    Figure CN119569453B_ABST
Patent Text Reader

Abstract

The application discloses a kind of graphene composite perovskite manganese oxide polycrystalline ceramics and preparation method and application thereof, belong to non-refrigeration high sensitivity infrared detection technical field.The chemical expression of the graphene composite perovskite manganese oxide polycrystalline ceramic is La 0.81 (Ca 0.03 Sr 0.16 )MnO3:G y Wherein, G is graphene, y is the mass fraction of graphene in perovskite manganese oxide composite powder, y=0.1~0.2%.The polycrystalline ceramic prepared by the application can reach more than 30% TCR value, T k Value is close to 300K, has excellent adaptability to room temperature work, has excellent sensitivity to temperature change, and can effectively improve the detection accuracy of non-refrigeration infrared detector when applied in non-refrigeration infrared detector.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of uncooled high-sensitivity infrared detection technology, and relates to a graphene composite perovskite manganese oxide polycrystalline ceramic, its preparation method and application. Background Technology

[0002] Uncooled infrared detectors utilize the unique thermal effect of infrared radiation, converting it into heat, which is then converted into an electrical signal by a sensitive element. Therefore, the sensitivity of the sensitive element to temperature changes directly affects the accuracy of the uncooled infrared detector. This sensitivity can be characterized by the temperature coefficient of resistivity (TCR). A higher TCR indicates a more significant change in resistance with temperature variations, meaning a higher TCR results in greater sensitivity and higher accuracy. Furthermore, uncooled infrared detectors are typically used at room temperature, the main difference being that they do not require cooling. The peak temperature of the TCR, T0, is the temperature coefficient of resistivity. k Equivalent to the operating temperature of the sensitive element material, T k The closer the TCR value is to room temperature, the better the room temperature performance of the sensitive element. Therefore, increasing the TCR value of the sensitive element and its T k A value closer to room temperature allows the sensitive element material to be better adapted to room temperature operation and to have higher sensitivity to temperature changes. This is of great significance for applying the sensitive element material to uncooled infrared detectors, thereby enabling the uncooled infrared detectors to have higher detection accuracy.

[0003] Currently, perovskite manganese oxides are mainly classified into two types: ABO3 and A2BO4. These two types differ significantly in structure. The perovskite manganese oxide of this invention belongs to the ABO3 type. However, due to defects and impurities at the grain boundaries of ABO3 perovskite manganese oxides, their electrical transport properties are affected, resulting in higher resistivity at the grain boundaries. When charge carriers pass through these regions, they are interfered with by scattering effects, reducing the mobility of itinerant electrons. This leads to a decrease in the TCR and T2BO4 of ABO3 perovskite manganese oxides. k The control effect is limited, and the high sensitivity of polycrystalline ceramics to temperature changes at room temperature cannot be effectively utilized, affecting the accuracy of uncooled infrared detectors.

[0004] Therefore, it is necessary to provide a graphene-composite perovskite manganese oxide polycrystalline ceramic, its preparation method, and its application, to improve the TCR value of the polycrystalline ceramic and simultaneously enhance its T... k The value is closer to room temperature. Summary of the Invention

[0005] To overcome the problems in the prior art, this invention employs advanced ultrasonic ball milling to prepare composite powder, combined with spark plasma sintering technology to prepare graphene-composite perovskite manganese oxide polycrystalline ceramics. Graphene nanosheets are distributed within the grain boundaries of the polycrystalline ceramic, with graphene primarily existing at grain boundaries. This effectively improves the grain boundary effect of the polycrystalline ceramic, enhances intergranular carrier migration efficiency, and significantly improves the conductivity of the polycrystalline ceramic, thereby increasing its TCR value. Furthermore, the polycrystalline ceramic of this invention has a higher TCR value. k The K value is close to 300K, which gives the polycrystalline ceramic of this invention excellent room temperature operating performance.

[0006] To achieve the above objectives, the present invention is implemented through the following technical solution:

[0007] This invention proposes a graphene-composite perovskite manganese oxide polycrystalline ceramic, wherein graphene nanosheets are distributed within the grain boundaries of the perovskite manganese oxide ceramic. The chemical formula of the graphene-composite perovskite manganese oxide polycrystalline ceramic is as follows:

[0008] La 0.81 (Ca 0.03 Sr 0.16 MnO3:G y Wherein, G represents graphene, and y represents the mass fraction of graphene in the perovskite manganese oxide composite powder, y = 0.1 to 0.2%.

[0009] Another aspect of the present invention provides a method for preparing the above-mentioned graphene composite perovskite manganese oxide polycrystalline ceramic, the method comprising the following steps:

[0010] (1) Weigh the raw materials La(NO3)3·6H2O, Sr(NO3)2, Ca(NO3)2 and Mn(NO3)2·4H2O according to the stoichiometric ratio, and prepare La using the sol-gel method. 0.81 (Ca 0.03 Sr 0.16 MnO3 precursor powder;

[0011] (2) Graphene is added to isopropanol and subjected to high-precision ultrasonic treatment to obtain a graphene dispersion solution. Then, the La obtained in step (1) is added to the dispersion solution. 0.81 (Ca 0.03 Sr 0.16 MnO3 precursor powder was added to a graphene dispersion solution, and an anionic surfactant was added simultaneously to obtain a mixed solution.

[0012] (3) The mixed solution obtained in step (2) is subjected to tip ultrasonic treatment, ball milling, and drying in sequence to obtain La. 0.81 (Ca 0.03Sr 0.16 MnO3:G y Composite powder;

[0013] (4) Under an inert gas pressurization environment, the La obtained in step (3) is subjected to... 0.81 (Ca 0.03 Sr 0.16 MnO3:G y The composite powder was subjected to spark plasma sintering (SPS) to obtain graphene-composite perovskite manganese oxide polycrystalline ceramic.

[0014] Preferably, in step (2), the amount of isopropanol used is related to the amount of La. 0.81 (Ca 0.03 Sr 0.16 The liquid-to-solid ratio of the MnO3 precursor powder is 10 mL: 3 g.

[0015] Preferably, the anionic surfactant is sodium dodecyl sulfate, and the sodium dodecyl sulfate reacts with La... 0.81 (Ca 0.03 Sr 0.16 The mass ratio of MnO3 precursor powder is 1:20.

[0016] Preferably, in steps (2) and (3), the ultrasonic treatment frequency of the tip is 25kHz, and the treatment is carried out at an amplitude of 10μm for 15s, followed by a 25s stop, and then repeated for a total of 3h. In step (3), the ball milling speed is 300rpm, the ball milling medium is isopropanol, the ball-to-material ratio is 2:1 to 5:1, and the ball milling time is 3h. The drying temperature is 55℃ and the drying time is 50min.

[0017] Preferably, in step (4), the inert gas is argon and the ambient pressure is 3 to 6.5 Pa.

[0018] Preferably, the spark plasma sintering process is as follows: first, the temperature is raised to 800°C at a heating rate of 100°C / min; then, the temperature is raised to 900–1500°C at a heating rate of 40°C / min, held for 10–20 min, and then the temperature is lowered to 600°C at a cooling rate of 50°C / min, after which La… 0.81 (Ca 0.03 Sr 0.16 MnO3:G y The composite powder was cooled to room temperature in the furnace.

[0019] Preferably, in step (1), La is prepared using the sol-gel method. 0.81 (Ca 0.03 Sr 0.16The specific process for obtaining MnO3 precursor powder is as follows: La(NO3)3·6H2O, Sr(NO3)2, Ca(NO3)2, and Mn(NO3)2·4H2O are weighed according to the stoichiometric ratio as raw materials. Citric acid is weighed according to a molar ratio of raw materials to citric acid of 1:2. The raw materials and citric acid are then dissolved in deionized water. Ethylene glycol is added according to a molar ratio of citric acid to ethylene glycol of 1:4 to obtain a mixed solution. The mixed solution is stirred and heated for 2 hours until it becomes viscous and foams, forming a wet sol. The wet sol is dried at 200°C for 12 hours to completely evaporate the water, obtaining a dry gel. The dry gel is ground for 30 minutes and then pre-sintered at 500°C for 10 hours to obtain La(NO3)3·6H2O. 0.81 (Ca 0.03 Sr 0.16 MnO3 precursor powder.

[0020] Preferably, the graphene has a purity of 99.9% and a specific surface area of ​​120–150 m². 2 / g, with an average flake thickness of 5–8 nm and an average particle size of 5–10 μm.

[0021] This invention also proposes the application of the above-mentioned graphene composite perovskite manganese oxide polycrystalline ceramic in uncooled infrared detectors.

[0022] The beneficial effects of this invention are:

[0023] 1. In this invention, graphene is incorporated into La as a second phase composite. 0.81 (Ca 0.03 Sr 0.16 MnO3 ceramics exist primarily in the form of grain boundary enrichment. Graphene can form conductive channels at grain boundaries, which is beneficial for electron conduction, improves charge transport behavior at grain boundaries, improves the grain boundary effect of polycrystalline ceramics, passivates defect states at grain boundaries, induces and improves the crystallization quality of polycrystalline ceramics, enhances the carrier migration efficiency between grains, and significantly improves the conductivity of polycrystalline ceramics, thereby increasing the TCR value of polycrystalline ceramics.

[0024] 2. This invention utilizes advanced ultrasonic processing to generate high-frequency vibrations and shear forces, effectively breaking down graphene agglomerates and dispersing them in a solvent. Simultaneously, it strengthens the bonding between graphene and La using anionic surfactants and ball milling. 0.81 (Ca 0.03 Sr 0.16 The dispersion and mixing uniformity of MnO3 precursor powder are improved, thereby preparing a more uniform polycrystalline ceramic composite.

[0025] 3. This invention generates high-frequency vibration and shear force through advanced ultrasonic processing, enabling...

[0026] La 0.81 (Ca 0.03 Sr 0.16 MnO3 precursor powder can produce finer grains, thereby generating more grain boundaries, providing more space for graphene interstitial filling, which is beneficial to enhancing electron transport and improving the electrical transport performance of polycrystalline ceramics.

[0027] 4. This invention, through spark plasma sintering (SPS), effectively reduces sintering time, avoids over-burning caused by graphene oxidation and uneven thermal expansion stress, and simultaneously enhances the bonding between graphene and La. 0.81 (Ca 0.03 Sr 0.16 Strengthening the interfacial bonding between MnO3 molecules reduces defects and porosity at the interface, which helps to improve the TCR value of polycrystalline ceramics.

[0028] 5. By performing SPS, this invention can effectively reduce dislocations at grain boundaries, reduce scattering effects, and improve electron mobility, which is beneficial for obtaining a larger TCR value.

[0029] 6. By performing SPS, this invention can concentrate high-energy pulse energy at the grain boundaries, which is beneficial for the precise filling and dispersion of graphene at the grain boundaries, and helps graphene to be optimally arranged at the grain boundaries to obtain the best electronic conduction effect. Attached Figure Description

[0030] Figure 1 La for graphene grain boundary composite 0.81 (Ca 0.03 Sr 0.16 Schematic diagram of MnO3 ceramics;

[0031] Figure 2 The images show the SEM surface morphology of the polycrystalline ceramic prepared in Example 1 of this invention, where (a) is a SEM surface morphology of the polycrystalline ceramic with a scale bar of 3 μm and (b) is a SEM surface morphology of the polycrystalline ceramic with a scale bar of 10 μm.

[0032] Figure 3 The images show the ρ-T curve and TCR-T curve of the polycrystalline ceramic prepared in Example 1, where (a) is the ρ-T curve and (b) is the ρ-T curve.

[0033] Figure 4 The images show the ρ-T curve and TCR-T curve of the polycrystalline ceramic prepared in Example 2, where (a) is the ρ-T curve and (b) is the ρ-T curve.

[0034] Figure 5 The images show the ρ-T curves and TCR-T curves of the polycrystalline ceramics prepared in Example 3, where (a) is the ρ-T curve and (b) is the ρ-T curve.

[0035] Figure 6 The figures show the ρ-T curve and TCR-T curve of the polycrystalline ceramic prepared in Example 4, where (a) is the ρ-T curve and (b) is the ρ-T curve. Detailed Implementation

[0036] The present invention will be further described in detail below with reference to specific embodiments.

[0037] Example 1:

[0038] This embodiment prepares polycrystalline ceramics using the following method:

[0039] (1) Accurately weigh 9.2512g La(NO3)3·6H2O (purity ≥99.0%), 0.8852g Sr(NO3)2 (purity ≥99.0%), 0.1861g Ca(NO3)2 (purity ≥99.0%), and 9.3094g Mn(NO3)2·4H2O (purity = 50.0%), and 21.9738g citric acid (chelating agent), and dissolve them in deionized water. Then add 8mL of ethylene glycol (gelling agent) to obtain a mixed solution. Stir the mixed solution and heat it for 2 hours. When the liquid becomes viscous and foams, a wet sol is formed. Place the wet gel in a drying oven and dry it at 200℃ for 12 hours to completely evaporate the water to obtain a dry gel. The dry gel was thoroughly ground in a mortar for 30 minutes, and then placed in a box furnace for pre-sintering at 500°C for 10 hours to obtain 6g of La. 0.81 (Ca 0.03 Sr 0.16 MnO3 precursor powder.

[0040] (2) Add 0.0072g of graphene to 20mL of isopropanol (y = 0.12%), and perform 15s of tip ultrasonic treatment at a frequency of 25kHz and an amplitude of 10μm, then stop for 25s, then perform 15s of tip ultrasonic treatment again, and stop for 25s again. Repeat this cycle for a total of 3h of tip ultrasonic treatment to obtain a graphene dispersion solution.

[0041] (3) The La prepared in step (1) 0.81 (Ca 0.03 Sr 0.16 When MnO3 precursor powder is added to a graphene dispersion solution, La is obtained. 0.81 (Ca 0.03 Sr 0.16 A mixed solution of MnO3 and graphene was prepared, and 0.3g of sodium dodecyl sulfate was added to prevent graphene agglomeration.

[0042] (4) The above mixed solution was subjected to 15s of tip ultrasonic treatment at a frequency of 25kHz and an amplitude of 10μm, then stopped for 25s, then subjected to 15s of tip ultrasonic treatment again, and then stopped for 25s again. This cycle was repeated for a total of 3 hours of tip ultrasonic treatment. Then, it was mixed with isopropanol medium at a speed of 300rpm in a planetary ball mill for 3 hours. The ball-to-material ratio during ball milling was 3:1.

[0043] (5) To evaporate and remove excess alcohol and sodium dodecyl sulfate, the ball-milled mixture from step (4) was placed in a rotary evaporator and dried at 55°C for 50 min to obtain...

[0044] La 0.81 (Ca 0.03 Sr 0.16 MnO3:G 0.12 Composite powder.

[0045] (6) Regarding La 0.81 (Ca 0.03 Sr 0.16 MnO3:G 0.12 The powder was sintered using SPS (Spectrophotometry). First, argon gas was introduced into the sintering furnace until the pressure reached 5 Pa. Then, the furnace was heated to 800°C at a rate of 100°C / min, followed by a further increase to 900°C at a rate of 40°C / min. After holding at this temperature for 10 minutes, the temperature was reduced to 600°C at a rate of 50°C / min, and then cooled to room temperature with the furnace. The final result was an L-shaped powder with a diameter of 20 mm and a thickness of 8 mm. a0.81 (Ca 0.03 Sr 0.16 MnO3:G 0.12 Polycrystalline ceramic bulk.

[0046] Scanning electron microscopy (SEM) experiments were performed on the polycrystalline ceramic bulk material prepared in this embodiment, and the results are as follows: Figure 2 As shown, the resistivity ρ of the polycrystalline ceramic bulk material prepared in this embodiment was measured, and the TCR value was calculated. The results are as follows. Figure 3 As shown, through Figure 2 It can be seen that the polycrystalline ceramic bulk prepared in this embodiment has a high degree of ceramic densification, good grain growth, uniform size, regular morphology, and good connectivity. No abnormal growth phenomenon was observed, and no other phases were observed.

[0047] pass Figure 3 It can be seen that the TCR value of the polycrystalline ceramic bulk material prepared in this embodiment reaches 18.51% / K; T k It reaches 303.28K, which is within the room temperature range.

[0048] Example 2:

[0049] This embodiment prepares polycrystalline ceramics using the following method:

[0050] (1) This embodiment uses the same method as in Example 1 to prepare La 0.81 (Ca 0.03 Sr 0.16 MnO3 precursor powder.

[0051] (2) Add 0.0084 g of graphene to 20 mL of isopropanol (y = 0.14%), and perform 15 s of tip ultrasonic treatment at a frequency of 25 kHz and an amplitude of 10 μm. Then stop for 25 s, and then perform 15 s of tip ultrasonic treatment again, and stop for 25 s again. Repeat this cycle for a total of 3 h of tip ultrasonic treatment to obtain a graphene dispersion solution.

[0052] (3) The La prepared in step (1) 0.81 (Ca 0.03 Sr 0.16 When MnO3 precursor powder is added to a graphene dispersion solution, La is obtained. 0.81 (Ca 0.03 Sr 0.16 A mixed solution of MnO3 and graphene was prepared, and 0.3g of sodium dodecyl sulfate was added to prevent graphene agglomeration.

[0053] (4) The above mixed solution was subjected to 15s of tip ultrasonic treatment at a frequency of 25kHz and an amplitude of 10μm, then stopped for 25s, then subjected to 15s of tip ultrasonic treatment again, and then stopped for 25s again. This cycle was repeated for a total of 3 hours of tip ultrasonic treatment. Then, it was mixed with isopropanol medium at a speed of 300rpm in a planetary ball mill for 3 hours. The ball-to-material ratio during ball milling was 2:1.

[0054] (5) To evaporate and remove excess alcohol and sodium dodecyl sulfate, the ball-milled mixture from step (4) was placed in a rotary evaporator and dried at 55°C for 50 min to obtain...

[0055] La 0.81 (Ca 0.03 Sr 0.16 MnO3:G 0.14 Composite powder.

[0056] (6) Regarding La 0.81 (Ca 0.03 Sr 0.16 MnO3:G 0.14The powder was sintered using SPS (Spectrophotometry). First, argon gas was introduced into the sintering furnace until the pressure reached 3 Pa. Then, the furnace was heated to 800°C at a rate of 100°C / min, followed by a further increase to 1100°C at a rate of 40°C / min. After holding at this temperature for 12 minutes, the temperature was reduced to 600°C at a rate of 50°C / min, and then cooled to room temperature with the furnace. The final result was an L-shaped powder with a diameter of 20 mm and a thickness of 8 mm. a0.81 (Ca 0.03 Sr 0.16 MnO3:G 0.14 Polycrystalline ceramic bulk.

[0057] The resistivity ρ of the polycrystalline ceramic bulk material prepared in this embodiment was measured, and the TCR value was calculated. The results are as follows: Figure 4 As shown.

[0058] pass Figure 4 It can be seen that the TCR value of the polycrystalline ceramic prepared in this embodiment reaches 25.25% / K; T k The K value reached 299.97 K, which is within the room temperature range. The grain morphology and growth morphology of the perovskite manganese oxide polycrystalline ceramic are similar to those in Example 1.

[0059] Example 3:

[0060] (1) This embodiment uses the same method as in Example 1 to prepare La 0.81 (Ca 0.03 Sr 0.16 MnO3 precursor powder.

[0061] (2) Add 0.0096g of graphene to 20mL of isopropanol (y = 0.16%), and perform 15s of tip ultrasonic treatment at a frequency of 25kHz and an amplitude of 10μm, then stop for 25s, then perform 15s of tip ultrasonic treatment again, and stop for 25s again. Repeat this cycle for a total of 3h of tip ultrasonic treatment to obtain a graphene dispersion solution.

[0062] (3) The La prepared in step (1) 0.81 (Ca 0.03 Sr 0.16 When MnO3 precursor powder is added to a graphene dispersion solution, La is obtained. 0.81 (Ca 0.03 Sr 0.16 A mixed solution of MnO3 and graphene was prepared, and 0.3g of sodium dodecyl sulfate was added to prevent graphene agglomeration.

[0063] (4) The above mixed solution was subjected to 15s of tip ultrasonic treatment at a frequency of 25kHz and an amplitude of 10μm, then stopped for 25s, then subjected to 15s of tip ultrasonic treatment again, and then stopped for 25s again. This cycle was repeated for a total of 3h of tip ultrasonic treatment. Then it was mixed with isopropanol medium at a speed of 300rpm in a planetary ball mill for 3h. The ball-to-material ratio during ball milling was 5:1.

[0064] (5) To evaporate and remove excess alcohol and sodium dodecyl sulfate, the ball-milled mixture from step (4) was placed in a rotary evaporator and dried at 55°C for 50 min to obtain...

[0065] La 0.81 (Ca 0.03 Sr 0.16 MnO3:G 0.16 Composite powder.

[0066] (6) Regarding La 0.81 (Ca 0.03 Sr 0.16 MnO3:G 0.16 The powder was sintered using SPS (Spectrophotometry). First, argon gas was introduced into the sintering furnace until the pressure reached 6.5 Pa. Then, the furnace was heated to 800°C at a rate of 100°C / min, followed by a further increase to 1200°C at a rate of 40°C / min. After holding at this temperature for 15 minutes, the temperature was reduced to 600°C at a rate of 50°C / min, and then cooled to room temperature with the furnace. The final result was an L-shaped powder with a diameter of 20 mm and a thickness of 8 mm. a0.81 (Ca 0.03 Sr 0.16 MnO3:G 0.16 Polycrystalline ceramic bulk.

[0067] The resistivity ρ of the polycrystalline ceramic bulk material prepared in this embodiment was measured, and the TCR value was calculated. The results are as follows: Figure 5 As shown.

[0068] pass Figure 5 It can be seen that the TCR value of the polycrystalline ceramic prepared in this embodiment reaches 33.58% / K; T k The temperature reached 298.65 K, which is within the room temperature range. The grain morphology and growth morphology of the perovskite manganese oxide polycrystalline ceramic are similar to those in Example 1.

[0069] Example 4:

[0070] (1) This embodiment uses the same method as in Example 1 to prepare La 0.81 (Ca 0.03 Sr 0.16 MnO3 precursor powder.

[0071] (2) Add 0.0108g of graphene to 20mL of isopropanol (y = 0.18%), and perform 15s of tip ultrasonic treatment at a frequency of 25kHz and an amplitude of 10μm, then stop for 25s, then perform 15s of tip ultrasonic treatment again, and stop for 25s again. Repeat this cycle for a total of 3h of tip ultrasonic treatment to obtain a graphene dispersion solution.

[0072] (3) The La prepared in step (1) 0.81 (Ca 0.03 Sr 0.16 When MnO3 precursor powder is added to a graphene dispersion solution, La is obtained. 0.81 (Ca 0.03 Sr 0.16 A mixed solution of MnO3 and graphene was prepared, and 0.3g of sodium dodecyl sulfate was added to prevent graphene agglomeration.

[0073] (4) The above mixed solution was subjected to 15s of tip ultrasonic treatment at a frequency of 25kHz and an amplitude of 10μm, then stopped for 25s, then subjected to 15s of tip ultrasonic treatment again, and then stopped for 25s again. This cycle was repeated for a total of 3 hours of tip ultrasonic treatment. Then, it was mixed with isopropanol medium at a speed of 300rpm in a planetary ball mill for 3 hours. The ball-to-material ratio during ball milling was 3:1.

[0074] (5) To evaporate and remove excess alcohol and sodium dodecyl sulfate, the ball-milled mixture from step (4) was placed in a rotary evaporator and dried at 55°C for 50 min to obtain...

[0075] La 0.81 (Ca 0.03 Sr 0.16 MnO3:G 0.18 Composite powder.

[0076] (6) Regarding La 0.81 (Ca 0.03 Sr 0.16 MnO3:G 0.18 The powder was sintered using SPS (Spectrophotometry). First, argon gas was introduced into the sintering furnace until the pressure reached 5 Pa. Then, the furnace was heated to 800°C at a rate of 100°C / min, followed by a further increase to 1300°C at a rate of 40°C / min. After holding at this temperature for 18 minutes, the temperature was reduced to 600°C at a rate of 50°C / min, and then cooled to room temperature with the furnace. The final result was an L-shaped powder with a diameter of 20 mm and a thickness of 8 mm. a0.81 (Ca 0.03 Sr 0.16 MnO3:G 0.18 Polycrystalline ceramic bulk.

[0077] The resistivity ρ of the polycrystalline ceramic bulk material prepared in this embodiment was measured, and the TCR value was calculated. The results are as follows: Figure 6 As shown.

[0078] pass Figure 6 It can be seen that the TCR value of the polycrystalline ceramic prepared in this embodiment reaches 26.97% / K; T k The temperature reached 295.15 K, which is within the room temperature range. The grain morphology and growth morphology of the perovskite manganese oxide polycrystalline ceramic are similar to those in Example 1.

[0079] Example 5

[0080] (1) This embodiment uses the same method as in Example 1 to prepare La 0.81 (Ca 0.03 Sr 0.16 MnO3 precursor powder.

[0081] (2) Add 0.012g of graphene to 20mL of isopropanol (y = 0.2%), and perform 15s of tip ultrasonic treatment at a frequency of 25kHz and an amplitude of 10μm, then stop for 25s, then perform 15s of tip ultrasonic treatment again, and stop for 25s again. Repeat this cycle for a total of 3h of tip ultrasonic treatment to obtain a graphene dispersion solution.

[0082] (3) The La prepared in step (1) 0.81 (Ca 0.03 Sr 0.16 When MnO3 precursor powder is added to a graphene dispersion solution, La is obtained. 0.81 (Ca 0.03 Sr 0.16 A mixed solution of MnO3 and graphene was prepared, and 0.3g of sodium dodecyl sulfate was added to prevent graphene agglomeration.

[0083] (4) The above mixed solution was subjected to 15s of tip ultrasonic treatment at a frequency of 25kHz and an amplitude of 10μm, then stopped for 25s, then subjected to 15s of tip ultrasonic treatment again, and then stopped for 25s again. This cycle was repeated for a total of 3 hours of tip ultrasonic treatment. Then, it was mixed with isopropanol medium at a speed of 300rpm in a planetary ball mill for 3 hours. The ball-to-material ratio during ball milling was 3:1.

[0084] (5) To evaporate and remove excess alcohol and sodium dodecyl sulfate, the ball-milled mixture from step (4) was placed in a rotary evaporator and dried at 55°C for 50 min to obtain...

[0085] La 0.81 (Ca 0.03 Sr 0.16MnO3:G 0.2 Composite powder.

[0086] (6) Regarding La 0.81 (Ca 0.03 Sr 0.16 MnO3:G 0.2 The powder was sintered using SPS (Spectrophotometry). First, argon gas was introduced into the sintering furnace until the internal pressure reached 3 Pa. Then, the furnace was heated to 800°C at a rate of 100°C / min, followed by a further increase to 1500°C at a rate of 40°C / min. After holding at this temperature for 20 min, the temperature was reduced to 600°C at a rate of 50°C / min, and then cooled to room temperature with the furnace. The final result was an L-shaped powder with a diameter of 20 mm and a thickness of 8 mm. a0.81 (Ca 0.03 Sr 0.16 MnO3:G 0.2 Polycrystalline ceramic bulk.

[0087] The polycrystalline ceramic prepared in this embodiment has similar properties to that in Example 4.

[0088] Example 6

[0089] (1) This embodiment uses the same method as in Example 1 to prepare La 0.81 (Ca 0.03 Sr 0.16 MnO3 precursor powder.

[0090] (2) Add 0.006 g of graphene to 20 mL of isopropanol (y = 0.1%), and perform 15 s of tip ultrasonic treatment at a frequency of 25 kHz and an amplitude of 10 μm. Then stop for 25 s, and then perform 15 s of tip ultrasonic treatment again, and stop for 25 s again. Repeat this cycle for a total of 3 h of tip ultrasonic treatment to obtain a graphene dispersion solution.

[0091] (3) The La prepared in step (1) 0.81 (Ca 0.03 Sr 0.16 When MnO3 precursor powder is added to a graphene dispersion solution, La is obtained. 0.81 (Ca 0.03 Sr 0.16 A mixed solution of MnO3 and graphene was prepared, and 0.3g of sodium dodecyl sulfate was added to prevent graphene agglomeration.

[0092] (4) The above mixed solution was subjected to 15s of tip ultrasonic treatment at a frequency of 25kHz and an amplitude of 10μm, then stopped for 25s, then subjected to 15s of tip ultrasonic treatment again, and then stopped for 25s again. This cycle was repeated for a total of 3 hours of tip ultrasonic treatment. Then, it was mixed with isopropanol medium at a speed of 300rpm in a planetary ball mill for 3 hours. The ball-to-material ratio during ball milling was 2:1.

[0093] (5) To evaporate and remove excess alcohol and sodium dodecyl sulfate, the ball-milled mixture from step (4) was placed in a rotary evaporator and dried at 55°C for 50 min to obtain...

[0094] La 0.81 (Ca 0.03 Sr 0.16 MnO3:G 0.14 Composite powder.

[0095] (6) Regarding La 0.81 (Ca 0.03 Sr 0.16 MnO3:G 0.14 The powder was sintered using SPS (Spectrophotometry). First, argon gas was introduced into the sintering furnace until the pressure reached 3 Pa. Then, the furnace was heated to 800°C at a rate of 100°C / min, followed by a further increase to 1100°C at a rate of 40°C / min. After holding at this temperature for 12 minutes, the temperature was reduced to 600°C at a rate of 50°C / min, and then cooled to room temperature with the furnace. The final result was an L-shaped powder with a diameter of 20 mm and a thickness of 8 mm. a0.81 (Ca 0.03 Sr 0.16 MnO3:G 0.14 Polycrystalline ceramic bulk.

[0096] The polycrystalline ceramic prepared in this embodiment has similar properties to that in Example 1.

[0097] Through Example 2 ( Figure 4 ) and Example 1 ( Figure 3 The comparison shows that the peak resistivity of polycrystalline ceramics decreases with increasing doping concentration. This is related to the improved intergranular connectivity of graphene through grain boundary recombination. Simultaneously, the TCR value of polycrystalline ceramics increases, mainly due to improvements in grain boundary scattering, electron-electron scattering, electron-phonon scattering, and electron-magneton scattering.

[0098] The TCR value of the polycrystalline ceramic prepared in Example 3 exceeded 30% / K, reaching 33.58% / K. k Also, the temperature is near room temperature (298.65 K), indicating that the polycrystalline ceramic of this invention can effectively improve the grain boundary effect of polycrystalline ceramics, passivate defect states at grain boundaries, and induce improved La. 0.81(Ca 0.03 Sr 0.16 The crystal quality of MnO3 material is improved, enhancing the carrier transport behavior between grains, thereby greatly improving the electrical transport performance of the composite material.

[0099] The polycrystalline ceramic prepared in Example 4 showed a slight increase in peak resistivity and a slight decrease in TCR value, but still exceeded 20% / K. This is because excessive graphene doping leads to the formation of larger aggregates, which may disrupt the conductive network in the polycrystalline ceramic, reducing effective conductive pathways and resulting in increased resistivity. This indicates that the graphene doping amount should not be too high. While the maximum graphene doping amount in this invention has a certain negative impact on the performance of the polycrystalline ceramic, the impact is minor and remains within the normal usable range.

[0100] In summary, the polycrystalline ceramics prepared by this invention have a high TCR value, while T k The value is close to 300K, which proves that the polycrystalline ceramic of the present invention has a high degree of sensitivity to temperature changes at room temperature. When used in uncooled infrared detectors, it can effectively improve the detection accuracy of uncooled infrared detectors.

[0101] Finally, it should be noted that the above preferred embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit it. Although the present invention has been described in detail through the above preferred embodiments, those skilled in the art should understand that various changes can be made to it in form and detail without departing from the scope defined by the claims of the present invention.

Claims

1. A graphene-composite perovskite manganese oxide polycrystalline ceramic, characterized in that: In the graphene-composite perovskite manganese oxide polycrystalline ceramic, graphene nanosheets are distributed within the grain boundaries of the perovskite manganese oxide ceramic. The chemical formula of the graphene-composite perovskite manganese oxide polycrystalline ceramic is La. 0.81 (Ca 0.03 Sr 0.16 MnO3:G y Wherein, G represents graphene, and y represents the mass fraction of graphene in the perovskite manganese oxide powder, y = 0.1~0.2%; The preparation method of the graphene composite perovskite manganese oxide polycrystalline ceramic includes the following steps: (1) Weigh the raw materials La(NO3)3·6H2O, Sr(NO3)2, Ca(NO3)2 and Mn(NO3)2·4H2O according to the stoichiometric ratio, and prepare La using the sol-gel method. 0.81 (Ca 0.03 Sr 0.16 MnO3 precursor powder; (2) Add graphene to isopropanol and perform high-precision ultrasonic treatment to obtain a graphene dispersion solution, and then add the La obtained in step (1). 0.81 (Ca 0.03 Sr 0.16 MnO3 precursor powder was added to a graphene dispersion solution, and an anionic surfactant was added simultaneously to obtain a mixed solution. (3) The mixed solution obtained in step (2) is subjected to tip ultrasonic treatment, ball milling, and drying in sequence to obtain La. 0.81 (Ca 0.03 Sr 0.16 MnO3:G y Composite powder; (4) Under an inert gas pressurization environment, the La obtained in step (3) is subjected to... 0.81 (Ca 0.03 Sr 0.16 MnO3:G y The composite powder was subjected to spark plasma sintering to obtain graphene composite perovskite manganese oxide polycrystalline ceramic. The spark plasma sintering process is as follows: first, the temperature is raised to 800℃ at a heating rate of 100℃ / min, then raised to 900~1500℃ at a heating rate of 40℃ / min, held for 10~20min, and then lowered to 600℃ at a cooling rate of 50℃ / min, after which La... 0.81 (Ca 0.03 Sr 0.16 MnO3:G y The polycrystalline ceramic was cooled to room temperature in the furnace.

2. The preparation method of graphene composite perovskite manganese oxide polycrystalline ceramic according to claim 1, characterized in that: The preparation method includes the following steps: (1) Weigh the raw materials La(NO3)3·6H2O, Sr(NO3)2, Ca(NO3)2 and Mn(NO3)2·4H2O according to the stoichiometric ratio, and prepare La using the sol-gel method. 0.81 (Ca 0.03 Sr 0.16 MnO3 precursor powder; (2) Add graphene to isopropanol and perform high-precision ultrasonic treatment to obtain a graphene dispersion solution, and then add the La obtained in step (1). 0.81 (Ca 0.03 Sr 0.16 MnO3 precursor powder was added to a graphene dispersion solution, and an anionic surfactant was added simultaneously to obtain a mixed solution. (3) The mixed solution obtained in step (2) is subjected to tip ultrasonic treatment, ball milling, and drying in sequence to obtain La. 0.81 (Ca 0.03 Sr 0.16 MnO3:G y Composite powder; (4) Under an inert gas pressurization environment, the La obtained in step (3) is subjected to... 0.81 (Ca 0.03 Sr 0.16 MnO3:G y The composite powder was subjected to spark plasma sintering to obtain graphene-composite perovskite manganese oxide polycrystalline ceramic.

3. The method for preparing a graphene-composite perovskite manganese oxide polycrystalline ceramic according to claim 2, characterized in that: In step (2), the amount of isopropanol used is related to La 0.81 (Ca 0.03 Sr 0.16 The liquid-to-solid ratio of the MnO3 precursor powder is 10 mL: 3 g.

4. The method for preparing a graphene-composite perovskite manganese oxide polycrystalline ceramic according to claim 2, characterized in that: The anionic surfactant is sodium dodecyl sulfate, and the sodium dodecyl sulfate reacts with La... 0.81 (Ca 0.03 Sr 0.16 The mass ratio of MnO3 precursor powder to sodium dodecyl sulfate is:La 0.81 (Ca 0.03 Sr 0.16 MnO3 = 1:

20.

5. The method for preparing a graphene-composite perovskite manganese oxide polycrystalline ceramic according to claim 2, characterized in that: In steps (2) and (3), the frequency of the ultrasonic treatment at the tip is 25kHz. The treatment is carried out at an amplitude of 10μm for 15s, followed by a 25s stop, and the cycle is repeated for a total of 3h. In step (3), the ball milling speed is 300rpm, the ball milling medium is isopropanol, the ball-to-material ratio is 2:1~5:1, and the ball milling time is 3h. The drying temperature is 55℃ and the drying time is 50min.

6. The method for preparing a graphene-composite perovskite manganese oxide polycrystalline ceramic according to claim 2, characterized in that: In step (4), the inert gas is argon, and the ambient pressure is 3~6.5 Pa.

7. The method for preparing a graphene-composite perovskite manganese oxide polycrystalline ceramic according to claim 2, characterized in that: In step (1), La is prepared by the sol-gel method. 0.81 (Ca 0.03 Sr 0.16 The specific process for obtaining MnO3 precursor powder is as follows: La(NO3)3·6H2O, Sr(NO3)2, Ca(NO3)2, and Mn(NO3)2·4H2O are weighed according to the stoichiometric ratio as raw materials. Citric acid is weighed according to a molar ratio of raw materials to citric acid of 1:

2. The raw materials and citric acid are then dissolved in deionized water. Ethylene glycol is added according to a molar ratio of citric acid to ethylene glycol of 1:4 to obtain a mixed solution. The mixed solution is stirred and heated for 2 hours until it becomes viscous and foams, forming a wet gel. The wet gel is dried at 200℃ for 12 hours to completely evaporate the water, obtaining a dry gel. The dry gel is ground for 30 minutes and then pre-sintered at 500℃ for 10 hours to obtain La(NO3)3·6H2O. 0.81 (Ca 0.03 Sr 0.16 MnO3 precursor powder.

8. A method for preparing a graphene-composite perovskite manganese oxide polycrystalline ceramic according to any one of claims 2-7, characterized in that: The graphene has a purity of 99.9% and a specific surface area of ​​120-150 m². 2 / g, with an average flake thickness of 5~8nm and an average particle size of 5~10μm.

9. The application of the graphene composite perovskite manganese oxide polycrystalline ceramic of claim 1 in an uncooled infrared detector.

Citation Information

Patent Citations

  • Lanthanum manganate-based ion-doped and graphene complex and preparation method and photocatalysis application thereof

    CN106622277A

  • Method for improving electrical transport property of polycrystalline ceramic

    CN108727026A